Predictors of Decision Making in Families at Risk for Inherited Breast/Ovarian Cancer - Mellon, Suzanne (2009)
OBJECTIVE: The purpose of this study was to identify factors associated with decision making about inherited cancer risk information within families and determine the interdependence between survivors’ and relatives’ decision making. DESIGN: A descriptive, cross-sectional design using a population-based sample of 146 dyads (N=292) was used. Analyses included multilevel modeling using the Actor-Partner-Interdependence Model MAIN OUTCOME MEASURE: Decision making was the main outcome, along with the pros and cons in making a decision regarding inherited cancer risk information. RESULTS: Overall, results indicate several individual and family factors that survivors and female relatives contribute toward their own and each other’s decision making about inherited cancer risk information. Individual factors included the individual’s perceptions of their family communication and their family’s cancer history. Among family dyadic factors, survivors and family members’ age, communication and coping style influenced the decision making of the other member of the dyad. Cancer worries and a monitoring coping style affected both seeking and avoiding decision making for survivors and their relatives. CONCLUSIONS: In view of the importance of genetic information upon family health outcomes, it is critical to address both individual and family factors that may influence decision making about cancer risk information and surveillance options for all members within the family.